Effects of resisted sprint training on sprint performance in high school baseball players - Sekine, Y.; Okada, J. (American Journal of Sports Science, 2016)
Resisted sprint training (RST) affects sprint speed in the acceleration phase, but there is no research regarding this for in adolescents. This study investigated the effects of RST on sprint speed and ground reaction force (GRF) in high school baseball players. Subjects were assigned to the resisted sprint group (RSG, n=10, loading 20% body mass), or the normal sprint group (NSG, n=9, without loading) and trained three days per week for eight weeks. Sprint speed [0-5, 5-10, 10-15, 15-20 and 0-20 meters (m)] and GRF [peak propulsive/resultant force, (PFpro/ PFres); impulse, (I); and ratio of force applied onto the ground (RF)] measured at the right and left foot at the start, the first step of the left foot (L1st), 5 m and 10m were assessed before and after training. In the RSG, a significant interaction was found for sprint speed at 0-5 m (p=0.028) and increased after training (p<0.0001). The 15-20 m sprint speed increased significantly in the NSG after training (p=0.022). The 0-20 m sprint speed increased significantly in both groups after training (RSG, p=0.001; NSG, p=0.041). Significant interactions were found for PFpro (p=0.015) and RF (p=0.0002) at the L1st in the RSG. PFpro (p=0.005), PFres (p=0.038) and RF (p=0.0002) at L1st increased significantly in the RSG. RST increased sprint speed in the early part of the acceleration phase by improving force production but prevented the improvement of sprint speed over 15 m. Combining RST and sprint training without loading improved sprint speed in the acceleration phase.